Isolation and evaluation of indigenous bacteria for the development of probiotics in the biocontrol of luminescent vibriosis in Penaeus monodon Fabricius - Torrento, Marlon C.
Lumiscent vibriosis caused by Vibrio harveyi is a major prblem in the culture of Penaeus monodon or black tiger shrimp. In an attempt to isolate indigenous probiotic bacteria with the ability to inhibit V. harveyi, eighty three bacterial isolates from a nuber of rearing waters were screened for vibriostatic activity by the modified sensitivity method. Of these, two strains identified to be Bacillus spp. were inhibitory to V. harveyi. The probiotic potential of one of these strains, Bacillus RB3, and two other vibriostic Pseudomonas spp. (Ps. aeruginosa JP4 and Ps. fluorescens CM1) was evaluated by adding these strains individually in rearing seawaters with P. monodon postlarvae 3. Results of the laboratory trials showed a significantly higher survival rate in the larvae (P<0.05) when treated with any of the vibriostatic bacteria when compared with the control (untreated). The performances of the three strains in protecting the shrimps were the same. To evaluate their effects on the diatom, Chaetoceros calcitrans, used to feed some stages of P. monodon larvae, bacterial interaction experiments were done. None of the three strains showed suppressive effects on the diatom nor were they inhibited by the latter. The results of this work provide baseline data on the application of these strains as probiotics in shrimp culture.